2020
DOI: 10.2139/ssrn.3561298
|View full text |Cite
|
Sign up to set email alerts
|

Using the Eye of the Storm to Predict the Wave of Covid-19 UI Claims

Abstract: We leverage an event-study research design focused on the seven costliest hurricanes to hit the US mainland since 2004 to identify the elasticity of unemployment insurance filings with respect to search intensity. Applying our elasticity estimate to the state-level Google Trends indexes for the topic "unemployment," we show that out-of-sample forecasts made ahead of the official data releases for March 21 and 28 predicted to a large degree the extent of the Covid-19 related surge in the demand for unemployment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Our ndings for the EU27 compare favourably to those by Aaronson et al (2020) for the US. Aaronson et al show that unemployment-related queries surged before the record increase in unemployment insurance claims, which peaked before the lock-down measures were implemented.…”
Section: Measuring the Effect Of Lock-down Measures On Online Search supporting
confidence: 57%
See 2 more Smart Citations
“…Our ndings for the EU27 compare favourably to those by Aaronson et al (2020) for the US. Aaronson et al show that unemployment-related queries surged before the record increase in unemployment insurance claims, which peaked before the lock-down measures were implemented.…”
Section: Measuring the Effect Of Lock-down Measures On Online Search supporting
confidence: 57%
“…1 In particular, we look at the consequences of the pandemic (and the measures enacted to ght it) on unemployment, which is an exceptionally worrisome feature of this crisis. There are indeed already signs of unprecedented demand for unemployment bene ts in the US (Aaronson et al, 2020;Goldsmith-Pinkham and Sojourner, 2020;Kahn et al, 2020) and of a loss of about 35 million jobs among OECD countries in March alone. 2 Further, the impact on seasonal activities such as tourism and agriculture on which several EU countries depends heavily might be particularly severe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous reduction in aggregate supply and aggregate demand in their model leads to a deep, persistent recession. Larson and Sinclair (2020) and Aaronson et al (2020) attempted to predict how the coronavirus crisis affected unemployment insurance (UI) claims in the U.S. Larson and Sinclair found that, including the dates when states declared a state of emergency due to COVID-19, a panel framework improved forecasts of initial UI claims over the 14 March to 16 May 2020 period. Aaronson et al employed Google Trends data in an event study of seven large hurricanes to calculate the elasticity of UI claims with respect to the intensity of searches on the topic "unemployment".…”
Section: Introductionmentioning
confidence: 99%
“…These are fast in the sense that they are often available on a daily basis with little, if any, lag. As such, they offer a close to real-time read on how the economy is performing [1][2][3] .…”
mentioning
confidence: 99%